2014
DOI: 10.1371/journal.pone.0105066
|View full text |Cite
|
Sign up to set email alerts
|

Autoreactivity to Glucose Regulated Protein 78 Links Emphysema and Osteoporosis in Smokers

Abstract: RationaleEmphysema and osteoporosis are epidemiologically associated diseases of cigarette smokers. The causal mechanism(s) linking these illnesses is unknown. We hypothesized autoimmune responses may be involved in both disorders.ObjectivesTo discover an antigen-specific autoimmune response associated with both emphysema and osteoporosis among smokers.MethodsReplicate nonbiased discovery assays indicated that autoimmunity to glucose regulated protein 78 (GRP78), an endoplasmic reticulum chaperone and cell sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…Autoimmune responses have also been implicated in COPD-associated emphysema, and identification of specific autoantibodies associated with emphysema offers potential novel therapeutic targets (e.g., anti-glucose-regulated protein 78 and anti-elastin) 44 .…”
Section: Lung Destruction -Emphysemamentioning
confidence: 99%
See 2 more Smart Citations
“…Autoimmune responses have also been implicated in COPD-associated emphysema, and identification of specific autoantibodies associated with emphysema offers potential novel therapeutic targets (e.g., anti-glucose-regulated protein 78 and anti-elastin) 44 .…”
Section: Lung Destruction -Emphysemamentioning
confidence: 99%
“…COPD patients with a history of ≥2 exacerbations in the previous year were randomized to 600-mg intravenous dose on day 1 (loading dose), followed by 300 mg subcutaneous (two 150-mg injections) every 4 weeks (Q4W) for a total of 14 doses (MED18968, n = 160; placebo, n = 164) 46 . The primary endpoint was a reduction in the annualized rate of moderate to severe COPD exacerbations 44 . MED18968 was well-tolerated but had no effect on the rate of moderate or severe exacerbations or health-related quality of life (HRQOL).…”
Section: Barcelona Respiratory Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, there is increasing data supporting the association of COPD and osteoporosis. The causative mechanisms underlying this association are still being investigated, but are likely modulated by gender, clinical phenotype (with a significant relationship to the severity of emphysema) and genetic predisposition [82][83][84][85].…”
Section: Body Mass Index Muscle Wasting and Osteoporosismentioning
confidence: 99%
“…The article by Lu et al (2) manifested that anti-citrullinated protein antibodies activated nuclear factor-kB and tumor necrosis factor-a through binding to citrullinated GRP78 via activated extracellular signal-related kinase 1/2 and Jun NH 2 -terminal kinase in rheumatic arthritis. The article by Bon et al (3) indicated that GRP78 autoimmune responses in smokers were associated with emphysema and osteoporosis. Furthermore, the article by Wang et al (4) suggested that GRP78 was the drug target of isoliquiritigenin to enhance breast cancer stem cell chemosensitivity.…”
mentioning
confidence: 99%